Histopathologic and immunological features of Imiquimod induced psoriatic mouse model - Zhong-zhou HUANG; Xiao-yan CHEN; Min XU; Xue-chen AI; Zeng-qi TANG; Qing GUO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To investigate the dermatopathologic and immunological features of Imiquimod induced psoriatic mice model. Methods: Twenty BALB/c mice were grouped in IMQ-model group and control group randomly, each had 10 mice. The IMQ-model mice received a daily topical dose of 62.5 mg of IMQ cream(5%) on the shaved back and left ear for 7 consecutive days. The control group mice were treated similarly with vaseline. The Psoriasis Area and Severity Index score and thickness of left ear were measured daily. The dorsal skin samples were evaluated using H&E section and immunohistochemistry test of Ki-67. The spleens were weighed and the splenocyte were counted. Flow cytometry was used for detection of T-helper-cell subsets. Results: Erythema, scaling, skin thickening and ear swelling appeared on day 2 and deteriorated gradually. The cumulative score kept increasing by day 7. Histologically, the skin of IMQ-model mice showed epidermal proliferation and proinflammatory cells infiltration resembling psoriasis vulgaris. The thickness of epidermis (t=15.12, P<0.001) and expression of Ki-67 (t=10.50, P<0.001) were increased in IMQ-model. The weight of spleen and cell-counting of splenocytes increased significantly in IMQ-model group. Compared with control group, the splenic Th1 and Th17 cells showed rise in both proportion and number (all P<0.05), but the Th2 cells did not show significant change(both P>0.05). Conclusion: Imiquimod induced psoriatic mouse model could resemble psoriasis vulgaris closely, which allowed further exploration of psoriasis.